Comparison of serum levels of calcium and magnesium among preeclamptic and normotensive pregnant women at Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria - Onyegbule, Onyema A.; Meludu, Samuel C.; Dioka, Chudi E.; Udigwe, Gerald O.; Udo, John N.; Ezidigboh, Azubuike N.; Atuegbu, Chidiadi C.; Osakue, Nosakhare (International Journal of Research in Medical Sciences, 2017)
Background:Despite numerous studies, the exact aetiology of pre-eclampsia remains unknown. Some studies have shown that supplementation of calcium and magnesium could ameliorate the effects of pre-eclampsia. The objective of this study was to compare the calcium and magnesium levels in the serum of Nigerian women with or without pre-eclampsia. Methods:In this study, serum calcium and magnesium levels were determined using atomic absorption spectrometry in 54 patients and 48 healthy normotensive pregnant women. The mean, standard deviation, Student’s‘t’ test and Pearson correlation were employed. Results:Serum calcium was significantly lower in patients than controls (9.17 ± 0.6 vs. 7.22 ± 0.5 mg/dl. P <0.001) (t test). Plasma Magnesium was significantly lower in patients than controls 13.19 ± 1.1 vs. 9.81 ± 0.7 mg/dl. P <0.001). The systolic and diastolic blood pressure showed significant inverse correlation with both calcium and magnesium (P<0.01). Conclusion:There was significant reduction in the levels of calcium and magnesium in patients with pre-eclampsia. Dietary supplementation of these trace elements may help to prevent pre-eclampsia.